PTEN expression in patients with carcinoma of the cervix and its association with p53, Ki-67 and CD31 - Loures, Luciano Fernandes; Cândido, Eduardo Batista; Vidigal, Paula Vieira Teixeira; Seabra, Mariana Ataydes Leite; Marco, Luiz Armando Cunha de; Silva Filho, Agnaldo Lopes da [UNESP] (FapUNIFESP (SciELO), 2014)
PURPOSE: To investigate protein expression and mutations in phosphatase and tensin homolog (PTEN) in patients with stage IB cervical squamous cell carcinoma (CSCC) and the association with clinical-pathologic features, tumor p53 expression, cell proliferation and angiogenesis. METHODS: Women with stage IB CSCC (n=20 – Study Group) and uterine myoma (n=20 – Control Group), aged 49.1±1.7 years (mean±standard deviation, range 27–78 years), were prospectively evaluated. Patients with cervical cancer were submitted to Piver-Rutledge class III radical hysterectomy and pelvic lymphadenectomy and patients in the Control Group underwent vaginal hysterectomy. Tissue samples from the procedures were stained with hematoxylin and eosin for histological evaluation. Protein expression was detected by immunohistochemistry. Staining for PTEN, p53, Ki-67 and CD31 was evaluated. The intensity of PTEN immunostaining was estimated by computer-assisted image analysis, based on previously reported protocols. Data were analyzed using the Student’s t-test to evaluate significant differences between the groups. Level of significance was set at p<0.05. RESULTS: The PTEN expression intensity was lower in the CSCC group than in the Control (benign cervix) samples (150.5±5.2 versus 204.2±2.6; p<0.001). Our study did not identify any mutations after sequencing all nine PTEN exons. PTEN expression was not associated with tumor expression of p53 (p=0.9), CD31 (p=0.8) or Ki-67 (p=0.3) or clinical-pathologic features in patients with invasive carcinoma of the cervix. CONCLUSIONS: Our findings demonstrate that the PTEN protein expression is significantly diminished in CSCC.

OBJETIVO: O objetivo do estudo foi investigar a expressão e mutações do PTEN em pacientes com Carcinoma de Células Escamosas (CCE) de Colo do Útero com estadiamento IB e sua associação com fatores prognósticos, expressão do p53, proliferação celular e angiogênese. MÉTODOS: Mulheres com diagnóstico de CCE de colo uterino em estágio IB (n=20) (casos) e mioma uterino (n=20) (controle) com idade de 49.1±1.7 foram acompanhadas. As pacientes com câncer de colo do útero foram submetidas a histerectomia Piver-Rutledge classe III associada a linfadenectomia pélvica e aquelas com mioma uterino a histerectomia vaginal. Amostras de tumor e colo normal foram retiradas para avaliação histológica e marcação imuno-histoquímica das proteínas PTEN, p53, ki-67 e CD 3. A intensidade imunohistoquímica do PTEN foi estimada por processamento de imagem digital a partir de protocolos pré-estabelecidos. Os dados foram analisados através do teste de qui - quadrado (χ2). O nível de significância foi considerado quando p < 0,05. RESULTADOS: A expressão do PTEN estava diminuída no grupo de pacientes com CCE em comparação ao grupo controle (150.5±5.2 versus 204.2±2.6; p<0.001). Nenhuma mutação no seqüenciamento genético dos nove exons do PTEN foi encontrada. Não houve associação estatisticamente significativa entre a expressão do PTEN e a expressão do p53 (p=0,969), Ki-67 (p=0.283) e CD 31 (p=0.817) ou fatores prognósticos anátomo-clínicos nas pacientes com carcinoma invasor do colo uterino. CONCLUSÕES: Este estudo demonstrou que o PTEN estava significativamente diminuído nas pacientes com CCE.
Expressão do PTEN em pacientes com carcinoma de colo uterino e sua associação com p53, Ki-67 e CD31
Keywords: Uterine cervical neoplasms; Immunohistochemistry; Gene expression; Antigens, neoplasm; Neoplasias do colo do útero; Imunohistoquímica; Expressão gênica; Antígenos de neoplasias